Sistem Kamera Pengamatan Bawah Laut - Pramana, Rozeff; Irawan, Henky (Jurnal Sustainable: Jurnal Hasil Penelitian dan Industri Terapan, 2017)
Observation cameras have been widely applied in various sectors of human life. Cameras are widely used for offices, schools, hospitals, and other public services. They are functioned as security, vehicle traffic monitor, and observation of a certain area. The use of the cameras as an observation is not only used on land but can also be used at sea and air. Areas which are dominated by oceans need to apply the right and effective surveillance cameras. Through this study, the cameras are designed for underwater observation. The cameras used are IP cameras which enable to be operated for surveillance systems up to dozens of meters below sea level. Underwater observation cameras also use an independent power supply through solar panels. Data delivery from cameras which are on the bottom of sea to users who are on land using a Wireless system in the form of a router located on sea surface. With addition of other supporting devices i.e. camera housing, and a computer/ a laptop, this research produces effective and efficient observation cameras. The purpose of this research is to design a camera system which can monitor images/videos under the sea remotely wirelessly by using computer/smart phone.